STUDENTS’ PERSPECTIVE AND EXPERIENCE TOWARD LEARNING VOCABULARY USING MOBILE GAME - Galih Jodi Lazarurizqi; Maman Suryaman (PROJECT (Professional Journal of English Education), 2022)
The increasing of technology bring great impact to humans’ life, including education. Learning English is very important this day, to be able fluent in English students need to learn vocabulary. Students face difficulty when they memorizing and defining vocabulary because there is a huge number of vocabulary, and the process of learning is boring. Mobile games can help students to learn vocabulary more interestingly. This study aims to investigate students' perspectives about learning vocabulary using a mobile game. The method used thematic data analysis from Braun & Clark. As a result student’ has positive preception and expereience about learning media to learn English vocabulary, the challenges that students face, when they learn using a mobile game, is the distraction of social media. Keywords:  Mobile Games, Vocabulary Learning